Sumak Kawsay is not Buen Vivir (Alternautas, 2022)
Nowadays, the paradigm of development-consumerism is responsible for the desolating panorama of social injustice and unrestrained exploitation of natural resources that leads to self-destruction of life on the planet (Huanacuni-Mamani, 2010). From the Global South, the voices that question in depth the philosophical and civilizational presuppositions of the Eurocentric developmental model are becoming stronger and more frequent. No one is surprised that these voices emanate from the population disillusioned by the promises of global culture (Álvarez, 2014; Estermann, 2013). From the Andes, a philosophical otherness arises, denominated "Andean Philosophy", which is a sapiential manifestation of an ancient tradition that questions the civilizational centrism of the Western (Estermann, 2015). The purpose of Andean's thought is reflected in the Sumak Kawsay.